2020
DOI: 10.1002/ange.202005048
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Syntheses of Kopsane Alkaloids via a PtCl2‐Catalyzed Intramolecular [3+2] Cycloaddition

Abstract: A concise and asymmetric total synthesis of five kopsane alkaloids that share a unique heptacyclic caged ring system was accomplished. The key transformation in the sequence involved a remarkable PtCl2‐catalyzed intramolecular [3+2] cycloaddition, which allowed for the rapid assembly of pentacyclic carbon skeletons bearing 2,3‐quaternary functionalized indoline. Expeditious construction of diverse indoline scaffolds with excellent control of diastereoselectivity demonstrated the broad scope and versatility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…In 2018 and 2020, Ma and colleagues accomplished the synthesis of four kopsane alkaloids [17] . In 2020, the Ye group reported their synthesis of five kopsane alkaloids [18] . In connection with our ongoing studies towards the total synthesis of indole alkaloids, [19] herein, we report the divergent total synthesis of (+)‐ N ‐carbomethoxy‐10,22‐dioxokopsane ( 2 ), (−)‐epikopsanol‐10‐lactam ( 3 ), (+)‐10,22‐dioxokopsane ( 4 ) and (+)‐ N ‐methylkopsanone ( 5 ).…”
Section: Figurementioning
confidence: 99%
“…In 2018 and 2020, Ma and colleagues accomplished the synthesis of four kopsane alkaloids [17] . In 2020, the Ye group reported their synthesis of five kopsane alkaloids [18] . In connection with our ongoing studies towards the total synthesis of indole alkaloids, [19] herein, we report the divergent total synthesis of (+)‐ N ‐carbomethoxy‐10,22‐dioxokopsane ( 2 ), (−)‐epikopsanol‐10‐lactam ( 3 ), (+)‐10,22‐dioxokopsane ( 4 ) and (+)‐ N ‐methylkopsanone ( 5 ).…”
Section: Figurementioning
confidence: 99%
“…It was found that the intramolecular [3 + 2] cycloaddition is a crucial step that provided a stereopure product in mild conditions. 48 Moreover, ligand-free PtCl 2 was used as a catalyst in dichloroethane solvent. The authors employed computational simulations to model the reaction focusing on the cyclization step.…”
Section: Case Studiesmentioning
confidence: 99%
“…In 2020, asymmetric and concise total syntheses of five kopsan alkaloids were disclosed by Ye and co-workers via deprotection of the tosyl group under ultrasonic irradiation as a key step [137] . Kopsine the first isolated member of Kopsia indole alkaloids family, as well as many kopsane alkaloids contain an indoline fused to a strained carbocyclic cage [138] , [139] , [140] .…”
Section: Applications Of Ultrasound In the Total Synthesis Of Bioactive Natural Productsmentioning
confidence: 99%
“…Kopsine the first isolated member of Kopsia indole alkaloids family, as well as many kopsane alkaloids contain an indoline fused to a strained carbocyclic cage [138] , [139] , [140] . The structure of kopsane alkaloids namely (-)-kopsanone , (+)-kopsanol, (-)-epikopsanol, (+)-10,22-dioxokopsane and (+)- N -methyl-10,22-dioxokopsane share a unique heptacyclic skeleton having six stereogenic centers, of which two are vicinal and quaternary [137] . This family of natural products has drawn continuous attention from the synthetic organic and biological community due to their interesting structural pattern and attracting biological activities including cholinergic, antirheumatism, and anti-inflammation effects [141] .…”
Section: Applications Of Ultrasound In the Total Synthesis Of Bioactive Natural Productsmentioning
confidence: 99%